A High Grain Diet Dynamically Shifted the Composition of Mucosa-Associated Microbiota and Induced Mucosal Injuries in the Colon of Sheep - Wang, Yue; Xu, Lei; Liu, Junhua; Zhu, Weiyun; Mao, Shengyong (Frontiers in Microbiology, 2017)
This study investigated the dynamic shifts in mucosa-associated microbiota composition and mucosal morphology in the colon of sheep fed a high grain (HG) diet. A total of 20 male sheep were randomly assigned to 4 groups (n = 5 for each). The sheep in first group received hay diet. The animals in other 3 groups were fed an HG diet for 7 (HG7), 14(HG14) or 28 (HG28) days, respectively. Colonic digesta samples were collected to determine the pH and the concentrations of volatile fatty acid (VFA) and lactate. The colonic mucosa was sampled to characterize the bacterial communities using Illumina MiSeq sequencing and to determine mRNA expression levels of cytokines and tight junction protein genes using quantitative real-time PCR. As time advanced, results revealed that colonic pH linearly decreased (P = 0.007), and the concentrations of total VFA linearly increased (P < 0.001). Microbial analysis showed that an HG diet linearly reduced (P < 0.050) the diversity and richness of the colonic microbiota. The principal coordinate analysis results showed that the colonic mucosa-associated bacterial communities of the four groups significantly shifted with number of days fed an HG diet. At the genus level, HG feeding significantly increased the relative abundance of some taxa including Prevotella, Coprococcus, Roseburia, and Clostridium_sensu_stricto_1, and decreased the proportion of Treponema, and the percentage of these taxa was not affected by days fed an HG diet. The microscopic examination showed that HG feeding caused the mucosal epithelial injury. The RT-PCR results showed that the mRNA expression of claudin-1 (P = 0.038), IL-1β (P = 0.045), IL-6 (P = 0.050), and TNF-α (P = 0.020) increased linearly with number of days fed an HG diet. The correlation analysis revealed significant correlation between the colonic mucosal mRNA expression of cytokines and mucosal bacterial composition. Generally, HG feeding increased colonic fermentation and altered colonic mucosal bacterial communities, which eventually caused colonic mucosal damage and led to colonic dysfunction, and these changes occurred gradually over at least 4 weeks.